A multilayer perceptron-based model applied to histopathology image classification of lung adenocarcinoma subtypes - Liu, Mingyang; Li, Liyuan; Wang, Haoran; Guo, Xinyu; Liu, Yunpeng; Li, Yuguang; Song, Kaiwen; Shao, Yanbin; Wu, Fei; Zhang, Junjie; Sun, Nao; Zhang, Tianyu; et al. (Frontiers in Oncology, 2023)
Objective Lung cancer is one of the most common malignant tumors in humans. Adenocarcinoma of the lung is another of the most common types of lung cancer. In clinical medicine, physicians rely on the information provided by pathology tests as an important reference for the fifinal diagnosis of many diseases. Thus, pathological diagnosis is known as the gold standard for disease diagnosis. However, the complexity of the information contained in pathology images and the increase in the number of patients far exceeds the number of pathologists, especially in the treatment of lung cancer in less-developed countries. Methods This paper proposes a multilayer perceptron model for lung cancer histopathology image detection, which enables the automatic detection of the degree of lung adenocarcinoma infifiltration. For the large amount of local information present in lung cancer histopathology images, MLP IN MLP (MIM) uses a dual data stream input method to achieve a modeling approach that combines global and local information to improve the classifification performance of the model. In our experiments, we collected 780 lung cancer histopathological images and prepared a lung histopathology image dataset to verify the effectiveness of MIM. Results The MIM achieves a diagnostic accuracy of 95.31% and has a precision, sensitivity, specificity and F1-score of 95.31%, 93.09%, 93.10%, 96.43% and 93.10% respectively, outperforming the diagnostic results of the common network model. In addition, a number of series of extension experiments demonstrated the scalability and stability of the MIM. Conclusions In summary, MIM has high classifification performance and substantial potential in lung cancer detection tasks.